Situational strategic planning as a tool for the promotion of man's health: experience report (Research, Society and Development, 2020)
Objective: to describe the experience of nursing students in carrying out actions to promote men's health as part of a multidisciplinary health team based on the implementation of strategic situational planning. Methodology: this is a descriptive study of the experience report type through practical activities developed in a family health strategy located in a municipality in Rio Grande do Sul. Results and Discussions: implementation of the action plan occurred on June 11, 2019, and 320 male workers from the urban and rural infrastructure secretariat participated. The activities provided included health promotion actions, such as blood pressure measurement; hemoglycotest; rapid tests for HIV / AIDS, syphilis, hepatitis, dental consultation, medical consultation and guidelines regarding men's health. Final Considerations: working with the strategic situational planning allowed the realization of the situational diagnosis, the structuring and organization of activities with different sectors of the health care network and the integration between teaching-service, showing the relevance of carrying out similar activities for the health training.